A geographical information system for ZETDC - Kwanisai, Onismo (Midlands State University, 2018)
The main motive behind the research was to derive an answer to the discovered problems of the current system of the Zimbabwe Electricity Transmission and Distribution (ZETDC) with regards to the way the fault reports were being carried out and the quality of services offered. The conduction of research through research methodologies such as questionnaires, observations as well as interviews led to problems identification such as being more manual since it does not allow the ZETDC electrical engineers locate the fault easily thus the engineers would manually search for the transformer without any given co-odinates of the transformer location hence the process is timeous leading to long response time to customer problems. Furthermore, the system doesn’t help management in calculating overtime and the effectiveness of employees since there is no time recorded in attending to faults, the engineers will sometimes claim more than their overtime leading to incompetence within the organization. However, the main aim of this project is to help the ZETDC electrical engineers to easily locate the transformers for instant response to reported electricity faults. The researcher saw it as key to develop a geographical information system for the ZETDC electrical engineers. The core emphasis on geographical information systems (GIS) is on remote sensing which is an essential tool for the data capturing to subsequently to be incorporated into a GIS and for real time monitoring of environmental conditions for operational management of electricity. The tools that were used in system development includes, PhP, Java script, Xampp, and Micro-media Dreamweaver. In addition the system’s major aim was to automate the manual system of ZETDC into a more reliable and less tedious system.